Research Results on the Problem of Health Preservation among Ukrainian Education Sector Employees during Martial Law - Danylchuk, Larysa; Stynska, Viktoriia; Shtyfurak, Vira; Byrko, Nadiia; Kravchyn, Tetiana (European Journal of Sustainable Development, 2025)
The aim of the article is to present the results of an empirical study on the issue of maintaining the health of Ukrainian education sector employees during martial law in six components – physical, mental, intellectual, social and spiritual health, as well as the level of recreational activity as a resource for recovery. The methods include theoretical approaches (analysis, synthesis, generalization), empirical research (questionnaires, surveys), mathematical data processing using Microsoft Excel and visualization of the results. The study has revealed critical physical exhaustion, chronic stress, emotional burnout, decreased cognitive functions, social isolation and loss of meaning in life. The level of physical and intellectual recreation was low. Respondents named the end of the war, increased wages, reduced bureaucratic burden, stabilization of the education reform and restoration of sanatorium and resort provision among the conditions for health preservation. Armed conflict and martial law have significantly affected the health of educators, especially those working in relocation, remote work without adequate support, or near active combat zones. Systematic psychological support, recovery programs, professional development, and institutional platforms for health preservation are needed. Further research includes the development of digital methodological resources, the implementation of state intersectoral programs, and the integration of psychological support into the professional activities of educators. Keywords: Health, Health Preservation, Education Workers, Martial Law, Professional Workload, Stress, Professional Burnout, Resilience, Recreational Activities.